2021
DOI: 10.3389/fpsyg.2021.595536
|View full text |Cite
|
Sign up to set email alerts
|

Meridian-Specific and Post-Optical Deficits of Spatial Vision in Human Astigmatism: Evidences From Psycho-Physical and EEG Scalings

Abstract: Previous studies have demonstrated that orientation-specific deprivation in early life can lead to neural deficits of spatial vision in certain space, and can even result in meridional amblyopia (MA). Individuals with astigmatism are the optimal and natural models for exploring this asymmetric development of spatial vision in the human visual system. This study aims to assess the contrast sensitivity function (CSF) and EEG signals along two principal meridians in participants with regular astigmatism when bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
1
3
0
2
Order By: Relevance
“…4 ). The results show for most participants (controls and astigmatic individuals), as expected 20 , a higher sensitivity for the vertical meridian, but no correlation with the perceptual bias in the grouping task. Thus, the measured bias implies that the astigmatic individuals perceive the horizontal dimension compressed relative to the vertical dimension, thus perceiving a horizontal organization at the array’s equilibrium point.…”
Section: Discussionsupporting
confidence: 74%
“…4 ). The results show for most participants (controls and astigmatic individuals), as expected 20 , a higher sensitivity for the vertical meridian, but no correlation with the perceptual bias in the grouping task. Thus, the measured bias implies that the astigmatic individuals perceive the horizontal dimension compressed relative to the vertical dimension, thus perceiving a horizontal organization at the array’s equilibrium point.…”
Section: Discussionsupporting
confidence: 74%
“…Another study 15 showed that adaptation to astigmatic blur is transferred to long-term memory that could be engaged when blur is reapplied or disengaged when blur is removed. Gu et al 28 suggest that neural adaptation after long-term exposure may play a key role in compensating for optical blur. Accordingly, during the developmental period, the oblique astigmatic participant is continuously exposed to mirror symmetry oblique blur, which may induce monocular competition that may increase the BR episodes.…”
Section: Discussionmentioning
confidence: 99%
“…We used vernier visual acuity (VVA) indicators to evaluate the treatment methods. This indicator is one of the main criteria that allows you to assess the ability of the visual analyzer to analyze objects of complex configuration [4,23]. Special attention should be paid to forming homogeneous groups to exclude errors in assessing the results of amblyopia treatment in patients with astigmatism.…”
Section: клінічна та експериментальна медицина / Clinical and Experim...mentioning
confidence: 99%
“…В результаті цього в оці одночасно існують два меридіани, в одному з яких ГЗ є вищою, ніж в іншому. Асиметрії рефракції, пов'язані з астигматизмом можуть бути причиною розвитку особливої форми амбліопії -меридіональної амбліопії (МА) [1,2,3,4,5]. МА проявляється селективним порушенням ГЗ при розрізненні контурів предметів певної орієнтації [3].…”
Section: вступunclassified
See 1 more Smart Citation